Hydrogenated Core–Shell MAX@K2Ti8O17 Pseudocapacitance with Ultrafast Sodium Storage and Long‐Term Cycling. Issue 18 (22nd May 2017) - Zou, Guodong; Guo, Jianxin; Liu, Xianyu; Zhang, Qingrui; Huang, Gang; Fernandez, Carlos; Peng, Qiuming
Abstract : Sodium‐ion batteries are considered alternatives to lithium‐ion batteries for energy storage devices due to their competitive cost and source abundance. However, the development of electrode materials with long‐term stability and high capacity remains a great challenge. Here, this paper describes for the first time the synthesis of a new class of core–shell MAX@K2 Ti8 O17 by alkaline hydrothermal reaction and hydrogenation of MAX, which grants high sodium ion‐intercalation pseudocapacitance. This composite electrode displays extraordinary reversible capacities of 190 mA h g −1 at 200 mA g −1 (0.9 C, theoretical value of ≈219 mA h g −1 ) and 150 mA h g −1 at 1000 mA g −1 (4.6 C). More importantly, a reversible capacity of 75 mA h g −1 at 10 000 mA g −1 (46 C) is retained without any apparent capacity decay even after more than 10 000 cycles. Experimental tests and first‐principle calculations confirm that the increase in Ti 3+ on the surface layers of MAX@K2 Ti8 O17 by hydrogenation increases its conductivity in addition to enhancing the sodium‐ion intercalation pseudocapacitive process. Furthermore, the distorted dodecahedrons between Ti and O layers not only provide abundant sites for sodium‐ion accommodation but also act as wide tunnels for sodium‐ion transport. Abstract : A new method is described to prepare core–shell Ti3 SiC2 @K2 Ti8 O17 composites bestowing high sodium‐ion intercalation pseudocapacitance by alkalization hydrothermal reaction and hydrogenation. High capacity and structural stability, especially at high rates, are achieved simultaneously. The method is highlighted by its simplicity and high yield and can be extended to prepare other MAX‐based electrode materials.